AVP modulation of the vestibular nucleus via V1b receptors potentially contributes to the development of motion sickness in rat. Issue 1 (December 2015) - Xu, Li-Hua; Tang, Guan-Rong; Yang, Juan-Juan; Liu, Hong-Xia; Li, Jian-Cheng; Jiang, Zheng-Lin
Abstract Background Arginine vasopressin (AVP) is considered to be an etiologic hormone in motion sickness (MS). The present study was designed to investigate whether individual differences in AVP expression in the paraventricular nucleus (PVN) and in modulation on the vestibular nucleus (VN) are involved in MS. Systemic application or microinjection of AVP into rat VN and rotatory stimulus were used to induce conditioned taste aversion (CTA) to 0.15 % saccharin sodium solution as a model of MS. Results Intra-VN use of SSR149415, an antagonist of V1b receptors (V1bRs), blunted CTA. AVP inhibited Ca2+ influxes through L-type Ca2+ channels and NMDA receptor channels in cultured VN neurones, but antagonised by SSR149415. More AVP and V1bRs were expressed respectively in the PVN and VN after rotatory stimulus, especially in rats susceptible to MS. In the VN, AVP content was low, the AVP mRNA was less expressed, a few AVP-positive fibres were sparsely distributed, and fewer AVP/synaptophysin-positive terminals were identified. Almost no fluoro-ruby-labelled AVP-positive neurones in the PVN were found with retrograde tracing from the VN. SNP analysis of the reported 9 sites of the AVP gene showed significant difference between the groups susceptible and insusceptible to MS at the site rs105235842 in the allele frequencies and genotypes. However, there was not any difference between these two groups in the SNP of the reported 38 sites of V1bR gene. Conclusions AVP, through its modulatory, possibly humoral action on the VN neurones via the mediation of V1bR, may contribute to the development of motion sickness in rats; AVP gene polymorphisms may contribute to the individual difference in the responsive expression of AVP in the PVN; and higher expressions of AVP in the PVN and V1bRs in the VN may contribute to the development of motion sickness in rats after vestibular stimulation.